Peculiarities of Prenatal Development of Lungs in Plain-Nosed (Vespertilionidae) and Horseschoe (Rhinolophidae) Bats - Kovalyova, I.M. (Вестник зоологии, 2002)
For the first time the prenatal development of lungs and their definitive structure were studied in representatives of plain-nosed bats (Vespertilionidae) and horseshoe bats (Rhinolophidae). The results of this investigation show that in the studied bats the laying of lungs being at the 14th stage of the embryogenesis, as well as their subsequent development right up to the 18th stage were of the same mode. However after the 18th stage the development of lungs in the studied plain-nosed bats was sharply different from that in horseshoe ones when forming the structure of these organs. The explanation of such a phenomenon is given in connection with distinctions in spatial reciprocal location of the thorax organs, the body, and the head during embryogenesis. The supposition about the probable mediated relation between the bats echolocation (namely methods of radiating signals) and the peculiarities of lungs structures was suggested.